The collectors (Collectors (Jacqueline West), 1, 1, 2018)
Van has always been an outsider. Most people don't notice him. But he notices them. And he notices the small trinkets they drop, or lose, or throw away--that's why his collection is full of treasures. Then one day, Van notices a girl stealing pennies from a fountain, and everything changes. He follows the girl, Pebble, and uncovers an underground world full of wishes and the people who collect them. Apparently not all wishes are good and even good wishes often have unintended consequences--and the Collectors have made it their duty to protect us. But they aren't the only ones who have their eyes on the world's wishes--and they may not be the good guys, after all.